Heteroaromatization with 4-phenyldiazenyl-1-naphthol. Part II: Synthesis of some new benzochromens, benzochromenopyrimidines, benzochromenotriazolopyrimidines, benzochromenopyrimidotriazepine and antimicrobial activities - Radini, Ibrahim Ali; Hamed, Hany Mostafa; Kharir, Mohammed Abdo Yahya; Elwahab, Ashraf Hassan Fekry Abd (European Journal of Chemistry, 2017)
Synthesis of several new of benzochromenes (4-7), benzochromenopyrimidines (8 and 9), 14-(4-chlorophenyl)-12-(phenyldiazenyl)-14H-benzo[7,8]chromeno[3,2-e][1, 2, 4]triazolo[1, 5-c]pyrimidines, 4-amino-16-(4-chlorophenyl)-14-(phenyldiazenyl)-16H-benzo[7’, 8’]chro-meno[2’,3’:4,5]pyrimido[1,6-b][1,2,4]triazepine-3-carbonitrile (10a-e, 13) and 9-(benz-ylideneamino)-7-(4-chlorophenyl)-5-(phenyldiazenyl)-7, 9-dihydro-8H-benzo[7,8]chromeno [2,3-d]pyrimidin-8-imine (12), form starting from 2-amino-4-(p-chlorophenyl)-6-phenyl-diazenyl-4H-benzochromene-3-carbonitrile (3). The structure of these new compounds was confirmed using IR, 1H NMR and 13C NMR as well as MS spectroscopy. The structure activity relationship studies of the target compounds in agreement with the in vitro essays and confirmed higher potent antimicrobial activity against some of the tested microorganisms. The structure-activity relationship study revealed that the antimicrobial activity of benzochromenopyrimido triazepine nucleus was more beneficial than benzochromeno-triazolopyrimidine nucleus for antimicrobial activity.